Continuing Severe Water Shortage in the Water‐Receiving Area of the South‐To‐North Water Diversion Eastern Route Project From 2002 to 2020 - Yuyue Xu; Zhao Gun; Jianwei Zhao; Jianli Chen; Qing Liu; Xing Cheng; Edwin H. Sutanudjaja; Jida Wang; Hehua Liu; Wenfeng Zhan (Water Resources Research)
Abstract The water‐receiving area of the South‐to‐North Water Diversion Eastern Route Project (SNWDP‐ER) is one of the most severely affected water‐shortage areas in China, and no previous study has been conducted on the changes in water storage in this area. In this study, we combined the latest Gravity Recovery and Climate Experiment (GRACE) And GRACE Follow‐On products with global models for the first time to analyze changes in water storages in this area from 2002 to 2020, and to investigate the effects of climate change and human activity on changes in water storage. We found that SNWDP‐ER aided the recovery of surface water (nongroundwater) with a recovery rate of 9.44 ± 1.65 mm/yr after its implementation, but had little effect on the recovery of groundwater and terrestrial water storage in the water‐receiving area. Before the SNWDP‐ER was implemented, the rates of decrease of groundwater and terrestrial water storage were only −1.59 ± 0.58 and −5.18 ± 0.75 mm/yr, respectively. After implementation, the rates of decrease of groundwater and terrestrial water storage were −17.7 ± 1.27 and −8.16 ± 1.18 mm/yr, respectively. Groundwater decline, accelerated by human activity and climate change, has led to an accelerated decline in terrestrial water storage. Effects of SNWDP‐ER and stringent policies reducing groundwater use, along with largely increased precipitation in North China on groundwater storage after year 2020 need to be examined in the future. Our results have important implications for the management and evaluation of SNWDP‐ER.